Sovereign risk premia in the European government bond market - Kerstin Bernoth; Jürgen von Hagen; Ludger Schuknecht (European Central Bank (ECB), 2004)
This paper provides a study of bond yield differentials among EU eurobonds issued between 1991 and 2002. Interest differentials between bonds issued by EU countries and Germany or the USA contain risk premia which increase with the debt, deficit and debt-service ratio and depend positively on the issuer's relative bond market size. Global investors' attitude towards credit risk, measured as the yield spread between low grade US corporate bonds and government bonds, also affects bond yield spreads between EU countries and Germany/USA. The start of the European Monetary Union had significant effects on the bond pricing of the member states.
Keywords: G12; E43; E62; H63; 330; asset pricing; determination of interest rates; Fiscal Policy; government debt